2012
DOI: 10.1128/jb.06583-11
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of the Marine Bacterium Vibrio campbellii DS40M4, Isolated from Open Ocean Water

Abstract: Vibrio sp. strain DS40M4 is a marine bacterium that was isolated from open ocean water. In this work, using genomic taxonomy, we were able to classify this bacterium as V. campbellii. Our genomic analysis revealed that V. campbellii DS40M4 harbors genes related to iron transport, virulence, and environmental fitness, such as those encoding anguibactin and vanchrobactin biosynthesis proteins, type II, III, IV, and VI secretion systems, and proteorhodopsin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…YM5-799. In addition to the cyclic triscatecholate siderophores, a linear (non-cyclized) triscatecholate siderophore, trivanchrobactin, was reported from the marine isolate Vibrio campbelli DS40M4 [18], [19]. Trivanchrobactin is a linear trimeric ester of the previously reported vanchrobactin, 2,3-DHB-D-Arg-L-Ser [20].…”
Section: Introductionmentioning
confidence: 93%
“…YM5-799. In addition to the cyclic triscatecholate siderophores, a linear (non-cyclized) triscatecholate siderophore, trivanchrobactin, was reported from the marine isolate Vibrio campbelli DS40M4 [18], [19]. Trivanchrobactin is a linear trimeric ester of the previously reported vanchrobactin, 2,3-DHB-D-Arg-L-Ser [20].…”
Section: Introductionmentioning
confidence: 93%
“…Phylogenetic analyses showed that the PR gene in this strain, and also the associated crt genes encoding the enzymes for synthesis of the PR chromophore retinal, were acquired through lateral gene transfer from outside of the family Vibrionaceae and even outside of the Gammaproteobacteria (Gómez‐Consarnau et al ., ). In addition to AND4, PR is also found in three closely related V. campbellii strains (Gómez‐Consarnau et al ., ; Amaral et al ., ; Dias et al ., ; Wang et al ., ). At present, most currently available genome‐sequences from members of the genus Vibrio pertain to disease‐associated strains (particularly V. cholerae ), and few belong to vibrios obtained directly from seawater.…”
Section: Introductionmentioning
confidence: 99%
“…, ; Sung, Pineda, Macrae, Sorgeloos & Bossier ; Haldar, Chatterjee, Sugimoto, Das, Chowdhury, Hinenoya, Asakura & Yamasaki ). Now, V. campbellii has become another important pathogen, and attracts more and more interests (Amarala, Silvaa, Santosa, Diasa, Lopesb, Edwardsa, Thompsond & Thompsona ; Dias, Thompson, Fishman, Naka, Haygood, Crosa & Thompson ).…”
Section: Introductionmentioning
confidence: 99%